Examining the co-movement between cryptocurrency uncertainty and central bank digital currency uncertainty - Thai Hong Le; Duc Anh Nguyen; Tu Thanh Vu (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
This paper investigates the dynamic co-movement between the Cryptocurrency Uncertainty indices and the Central Bank Digital Currency Uncertainty indices. We apply the wavelet coherence framework using weekly data from January 13, 2017, to December 30, 2022. The empirical results reveal the significant co-movement between the Cryptocurrency Uncertainty Indices and the Central Bank Digital Currency Uncertainty Indices. Our findings suggest that the Cryptocurrency Policy Uncertainty index is highly correlated with the Central Bank Digital Currency Uncertainty index in the medium and long term but with the Central Bank Digital Currency Attention index in the short term. Our findings thus indicate that the Cryptocurrency Policy Uncertainty index can be used to predict the Central Bank Digital Currency Uncertainty index. On the other hand, the Cryptocurrency Environmental Attention index has historically correlated with the Central Bank Digital Currency Uncertainty indices in terms of long frequency.